Elementos para construção das especificidades na formação do educadorda EJA - Fernanda Aparecida Oliveira Rodrigues Silva (2013)
The aim of this study is to contribute to the discussion on the specificities of the training of the educator for youth and adult education (YAE) work. Four projects of youth and adult education were studied the Basic Education Project for Young People and Adults (PROEF II/CP) developed by the Faculty of Education of the Federal University of Minas Gerais (FAE/UFMG), the Paranoá Project run by the University of Brasília(UnB/DF), the Paulo Freire Municipal Centre for Worker Education (the Municipal government of Porto Alegre/RS) and the Zé Peão SchooL Project developed jointly by the Federal University of Paraiba (UFPB) and the Building Workers Trade Union (SINTRICOM). The investigation whichadopted a qualitative approach makes use of and consolidates a data bank resulting from two previous research projects on the same theme and carried out a literature review on practices of teacher training including movements of popular education and culture. Our analytical reading of the material and interpretation of the interviews allow us to affirm that during twenty years of activities each project sought and seeks to adopt a repertoire of training procedures which meets their specific needs, some of which have taken root during the Projects trajectory and have achieved certain stability and constitute lines of action with a doubleintentionality. One is directed at the construction of a concept of youth andadult education and the other involved the maintenance of this same concept. These lines of action are what we call key-ideas. We highlightthe following founding key-ideas: process centralized on the student; permanent orientation of the educator by a multidisciplinary group; historical contextualization of YAE and the project itself; and reality of the student as a pedagogical principle. And maintaining principles: elaboration of their own didactical tools; regular systematization and constant accompaniment of the work in the classroom. Having emphasized these key-ideas, we sought to substantiate them with the support of the literature from the general field of training and that of youth and adult education. From the arguments elaborated we conclude that the key-ideas are potential elements for the construction of a set of specificities for the training of the educator for YAE.